Allocation of New Goodwill After Termination of the Trademark Licensing Contract - Minghua Shi (Studies in Law and Justice, 2024)
The allocation of new goodwill between licensor and licensee after termination of the trademark licensing contract is an increasingly important and highly controversial issue in theory and practice in trademark licensing. The new goodwill is a special intangible property, which is a prerequisite for allocating the new goodwill. Based on Locke’s Labor Theory of Property and the principle of balance of interests, the allocation of new goodwill can be theoretically justified. Considering the separability of goodwill from trademarks and the valuability of goodwill, it is feasible to allocate new goodwill in practice. How do we allocate the newly generated goodwill? There are no express stipulations in-laws. Firstly, this article suggests that the allocation of new goodwill shall only be considered when the following three conditions are met: (1) there is no agreement between the parties on the ownership of the new goodwill or such agreement is unclear; (2) the licensee has contributed to the new goodwill; and (3) the new goodwill is significantly value-added. Secondly, based on contribution, we should consider various factors such as the degree of quality control, type of license and duration of license as the allocation standard of new goodwill. Finally, in actual operations, we need to make corresponding judgments based on different situations.